Imaginary Numbers and the Power of Artificial Intelligence (Journal of the College of Basic Education, 2026)
The paper titled \"Imaginary Numbers and the Power of Artificial Intelligence\" investigates the enormous importance of imaginary numbers in boosting the performance levels of some particular AI technologies in deep learning, signal processing, and simulations of complex systems. Imaginary numbers, being multiples of the imaginary unit where (i^2=-1) and being an imaginary number, also are said to belong to the complex number system, where from every real number we can extend to the complex plane. This extension enables extra dimensions of calculative ability i.e. the AI systems can solve ultra complex and non-linear problems where real numbers are ineffectual.Once imaginary numbers were the realm of books and of an abstract branch of mathematics and physics. Now they are essential in practical implementations across AI disciplines. In complex-valued neural network architectures, for example, we need complex-valued neurons to deep model the many intricate and complex patterns and dynamics, which are essential for the tasks of processing audio, images, and smoothly and efficiently handling all the components of electromagnetic waves. Complex numbers are also used in Fourier transforms, an important and essential tool of signal processing. These transforms temporally and spectrally code a signal, thus converting it from one domain to the other, enhancing the AI systems\' ability for higher order and intelligent tasks.The review of literature demonstrates the primary usefulness of imaginary numbers in growing the theory of complex numbers most especially in its application in the AI. Complex numbers help in the improvement of neural network models in particular in the area of power systems analysis and load-flow calculations. With the aid of complex numbers, the further development of certain techniques used in Information Retrieval is achieved through the use of Complex Hilbert Spaces. Also, the theory of electromagnetism and fluid dynamics which is based on complex analysis, makes use of imaginary numbers.In a certain method, the focus of the paper is on the theorems and properties pertaining to imaginary numbers and its application to solving equations which real numbers cannot, not to mention its application in other fields of sciences. The study of complex numbers involves the use of various techniques of algebraic manipulation and geometric representation as well as calculus.Case studies prove that complex numbers can be integrated into AI. Another application of complex numbers in AI Communication is FFT (Fast Fourier Transform) used in the domain of signal processing. In Quantum computing, complex numbers and AI are merged to analyses molecular structures efficiently. As an example, listening to audio was significantly improved by CVNN (Code Vons Neumann) which employed architectures capable of processing complex data. The application of AI technology in complex spheres has also made the imaginary number become top